ANALYSIS OF THE EFFECTIVENESS OF ACCIDENT INSURANCE COMPENSATION SETTLEMENT FOR PUBLIC TRANSPORTATION PASSENGERS AT PT. JASA RAHARJA REPRESENTATIVE OF TK II PADANG SIDEMPUAN - Harahap, Ayu Ashara; Nasution, Annio Indah Lestari; Jannah, Nurul (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2022)
This study aims to determine how the effectiveness of compensation settlement has been running effectively or ineffectively in accordance with the operational standards of PT. Jasa Raharja tk II padang sidempuan. This study used qualitative descriptive method with data collection of interviews, observations, documentation.Â The sample of this research is the company PT. Jasa Raharja Representative of TK II Padangsidimpuan, using descriptive analysis techniques which include: data reduction, data presentation, and conclusions. Specifically, that the data above shows the number of victims who have been disbursed compensation funds and their effectiveness is good and the settlement is timely. The measurement of effectiveness in general and most prominent is program success, goal success, satisfaction with the program, input and output levels, achievement and overall goals. Program effectiveness can be carried out with operational capabilities in carrying out work programs in accordance with predetermined goals. It is known that the analysis of the effectiveness of the settlement of accident insurance compensation for public transportation passengers at PT Jasa Raharja TK II Padang Sidempuan has been very good and effective. and all programs on the road at PT jasa raharja tk ii padang sidempuan have reached the desired target.Keywords: Accident Insurance; Indemnification; Effectiveness